Financial Instruments In The Capital Market - Alfiqri, M Reza (Journal of Accounting and Management, 2024)
Capital market instruments are traded in the form of securities that can be bought and sold by their owners, either ownership or debt capital market instruments. Ownership capital market instruments are realized in the form of shares, while debt instruments are realized in the form of bonds. There are 5 types of capital market instruments such as: stocks, bonds, mutual funds, warrants and rights.